THE EFFECT OF COOPERATIVE KAGAN STRUCTURES SUPPORTED BY HYPERMEDIA ON LEARNING THE (100X4) RELAY ACTIVITY - Abd Ali Kadhim, Mayasa; Abdulrasool, Tiba Hussein; Hasan Aldewan, Lamyaa; Jawad Kazem, Sanaa (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2025)
This research focuses on improving the learning of the technical stages of the 4×100m relay event, addressing the challenge that teaching these stages often depends on the command style, which has been shown to be ineffective in engaging students and enhancing their performance. The study aims to develop educational units using Kagan cooperative structures supported by hypermedia and evaluate their impact on learning. Using an experimental method with pre- and post-tests, the researcher compared an experimental group taught using Kagan cooperative structures and hypermedia with a control group taught using the traditional command style. The findings revealed that both groups positively impacted beginners' learning of the technical stages, but the experimental group, which used Kagan cooperative structures with hypermedia, outperformed the control group in terms of technical performance. Additionally, the use of heterogeneous grouping in the experimental group improved the performance of weaker students and motivated high- performing ones. This research highlights the effectiveness of interactive and cooperative learning strategies in improving technical performance in the 4×100m relay event.